(untitled) (Journal of Libya for geographical studies, 2024)
The phenomenon of urban sprawl is one of the most important issues that countries around the world suffer from, as it affects the sustainability of their agricultural lands and leads to their shrinkage and contraction, The problem of this study lies in the fact that the agricultural lands in the Wadi Kaam project are witnessing urban expansion, This phenomenon negatively affects the future of agricultural activity, This study aims to determine the spatial and temporal changes of urban sprawl on lands in the Wadi Kaam agricultural project in the period between 2004 and 2023, Given the difficulty of determining this impact, modern methods and techniques of remote sensing and geographic information systems were used, in addition to integrating their outputs with some quantitative techniques to achieve a broader understanding. For this phenomenon, the study used Landsat visuals for the years 2004-2013-2023, showing that the size of urban sprawl has developed from 4.26 hectares in the year 2004 to 11.26 hectares in the year 2023, Quantitative techniques have shown that the urban expansion density index indicates the occurrence of high-speed urban growth in the study area. In light of these results, the study emphasizes the necessity of developing future policies and plans to reduce the phenomenon of urban sprawl on agricultural lands.